Fisheries buybacks (Blackwell, 2007)
Fisheries buybacks are an important strategy being implemented globally in the efforts to produce a more sustainable and profitable fisheries' industry. Fisheries Buybacks provides the reader with an overview of buybacks and the issues surrounding them as well as a synthesis of the literature on this subject of growing importance. Alongside this material are eleven case studies from around the world that look at real life applications of buybacks and its successes and failures. Edited by two leading fisheries economists with chapters contributed by international experts in the field, Fisheries Buybacks will be a valuable resource for fisheries managers, economists, researchers, and policy makers for years to come.